1999
DOI: 10.1104/pp.119.2.785
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Transport and Not Photoinhibition Limits Growth of the Freshwater Cyanobacterium Synechococcus Species PCC 6301 at Low Temperature1

Abstract: The effect of low temperature on cell growth, photosynthesis, photoinhibition, and nitrate assimilation was examined in the cyanobacterium Synechococcus sp. PCC 6301 to determine the factor that limits growth. Synechococcus sp. PCC 6301 grew exponentially between 20°C and 38°C, the growth rate decreased with decreasing temperature, and growth ceased at 15°C. The rate of photosynthetic oxygen evolution decreased more slowly with temperature than the growth rate, and more than 20% of the activity at 38°C remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…Moreover, as other members of Oscillatoriales, it is well adapted to extremely low irradiance compared to other filamentous Cyanophyta (Albertano et al, 2000). The presence of Synechococcus and of the closely related Cyanobium bacillare in sampling points 1 and 2 of SC confirms that the average temperature of SC during the year is not particularly low, since this species does not thrive in cold environments (Sakamoto and Bryant, 1999). Synechococcus is not a typical cave organism: its occurrence has been reported on both marble and granite monuments in different Mediterranean countries (Crispim and Gaylarde, 2005), and it also can grow endolithically (Saiz-Jimenez et al, 1990).…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, as other members of Oscillatoriales, it is well adapted to extremely low irradiance compared to other filamentous Cyanophyta (Albertano et al, 2000). The presence of Synechococcus and of the closely related Cyanobium bacillare in sampling points 1 and 2 of SC confirms that the average temperature of SC during the year is not particularly low, since this species does not thrive in cold environments (Sakamoto and Bryant, 1999). Synechococcus is not a typical cave organism: its occurrence has been reported on both marble and granite monuments in different Mediterranean countries (Crispim and Gaylarde, 2005), and it also can grow endolithically (Saiz-Jimenez et al, 1990).…”
Section: Resultsmentioning
confidence: 74%
“…Several studies indicated that nitrate uptake suffers inhibition by the presence of ammonium (McCarthy et al 1982, Mitamura et al 1995, Tang et al 1997, Sakamoto & Bryant 1999. When ammonium and nitrate are both present, ammonium is generally preferred, although the complete suppression of the nitrate uptake is rare (Syrett 1981).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature showing that temperature affects cell composition, short-term nutrient uptake and, in particular, nitrogen metabolism (see Morris et al 1974, Yoder 1979, Terry 1983, Raimbault 1984, Whalen & Alexander 1984, Thompson et al 1992, Reay et al 1999, Sakamoto & Bryant 1999. These effects, while more subtle than those on growth and photosynthesis, can have enormous implications at the level of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%